A regional population‐based hereditary breast cancer screening tool in Italy: First 5‐year results. (11th February 2020) - Cortesi, Laura; Baldassarri, Bruna; Ferretti, Stefano; Razzaboni, Elisabetta; Bella, Mariangela; Bucchi, Lauro; Canuti, Debora; De Iaco, Pierandrea; De Santis, Giorgio; Falcini, Fabio; Galli, Vania; Godino, Lea; et al.
Abstract: Background: Up to 10% of individuals with breast cancer (BC) belong to families with hereditary syndromes. The aim of this study was to develop an instrument to identify individuals/families at high‐hereditary risk for BC and offer dedicated surveillance programs according to different risks. Methods: The instrument consisted of a primary questionnaire collecting history of BC and ovarian cancer (OC). This questionnaire was applied to women enrolled in the Emilia‐Romagna Breast Cancer Screening Program. General practitioners (GPs) and specialists could propose the same questionnaire too. Women with a score of ≥ 2, were invited to complete an oncogenetic counseling. According to the Tyrer‐Cuzick evaluation, women considered at high risk were invited to involve the most representative alive individual of the family affected with BC/OC for BRCA1/2 genetic testing. Results: Since January 2012 and December 2016, 660 040 women were evaluated by the regional screening program, of which 22 289 (3.5%) were invited to the Spoke evaluation, but only 5615 accepted (25.2%). Totally, also considering women sent by GPs and specialists, 11 667 were assessed and 5554 were sent to the Hub evaluation. Finally, 2342 (42.8%) women fulfilled the criteria for genetic testing, and 544 (23.2%) resulted BRCA1/2 mutation carriers. Conclusions: To our knowledge, this is the first regional population‐based multistep model that is aimed to identify individuals with BRCA1/2 mutations and to offer an intensive surveillance program for hereditary‐high risk women. This tool is feasible and effective, even if more efforts must be performed to increase the acceptance of multiple assessments by the study population. Abstract : This is, to our knowledge, the first multistep approach, including regional breast cancer screening program, general practitioners and specialists, aimed to identify individuals with BRCA1/2 mutations and to offer an intensive surveillance program for hereditary, high and intermediate risk women. Our results show that a regional population‐based model is feasible, even if more efforts have to be yielded to increase the acceptance of subsequent assessments from women at risk.